Skull Vibration-Induced Nystagmus Reveals Hidden Vestibular Asymmetry Dissociated from vHIT, VEMPs and Velocity-Storage-Related Responses: A Clinical–Physiological Case Series and Temporal-Domain Hypothesis - Leonardo Manzari (Audiology Research, 2026)
Background/Objectives: Skull vibration-induced nystagmus (SVIN) is a robust sign of vestibular asymmetry, yet its relationship with tests of impulsive canal function, short-latency otolithic reflexes, and sustained visuo-vestibular processing remains incompletely defined. To describe four clinical–physiological cases in which SVIN was dominant or disproportionate relative to the canal, otolithic-reflex, and sustained-domain profiles, and to propose a temporal-domain interpretation of this physiological non-congruence. Methods: Four patients with persistent disequilibrium, episodic vertigo, or selective vestibular-reflex dissociation underwent multidomain neuro-otological assessment, including bedside examination, video head impulse test/head impulse paradigm (vHIT/HIMP), suppression head impulse paradigm (SHIMP) when available, cervical and ocular vestibular-evoked myogenic potentials (cVEMPs and oVEMPs), rotatory or caloric testing when available, and optokinetic or other visuo-vestibular paradigms. SVIN was elicited by 100-Hz mastoid vibration and characterized by direction, dimensionality, stimulation-site dependence, reproducibility, and slow-phase velocity when available. Results: SVIN remained clinically informative across patients with preserved, minimally abnormal, or selectively dissociated canal and otolithic-reflex findings. The recurring feature was not normality of all conventional tests, but physiological non-congruence between the vibration-induced ocular response and the canal, otolithic-reflex, or sustained-domain profile. One patient showed normal six-canal vHIT and symmetric VEMPs despite an exceptionally large fixed-direction SVIN; another showed selective cVEMP absence with preserved oVEMPs and normal vHIT. Atypical multidimensional SVIN coexisted with marked optokinetic directional asymmetry in the adolescent case. Conclusions: SVIN is not a surrogate for vHIT, VEMPs, caloric, rotatory, or velocity-storage-related testing. It should be interpreted as a distinct phase-locked probe of vibration-sensitive vestibular imbalance. Irregular afferents provide the supported physiological framework, whereas dimorphic afferents represent a plausible, hypothesis-generating bridge population capable of contributing to otherwise unexplained clinicophysiological dissociations.